Developing non-aqueous slurry for CO2 capture - Sahar Foorginezhad; Xiaoyan Ji (Carbon Capture Science & Technology)
The urgency of mitigating CO2 emissions has become increasingly critical due to their detrimental effects on environmental sustainability and human health. Among emerging solutions, deep eutectic solvents (DESs) have garnered attention for their high CO2 capture capacities. However, widespread application of DESs has been constrained by their inherent high viscosity and cost. To overcome these limitations, this study further explores the novel strategy, where cosolvent addition and immobilization are combined to develop a non-aqueous slurry for CO2 capture with high efficiency. Here, [MEACl][EDA] with (1:5) molar ratio is mixed with ethylene glycol (EG) to form a non-aqueous DES solution, and the DES is further immobilized into the mesoporous silica to form a composite and then mixed with the DES-EG solution to make a slurry. The CO2 capture tests demonstrated 15 wt.% capture capacity at 22 °C and 1 bar, and efficient sorption and desorption rates (0.34 and 0.38 mol CO2/(kg sorbent·min) within the initial 2 min). The slurry also exhibited promising cyclic performance with 96.4 % recovery together with minimal solvent loss of 0.97 % and almost intact structure after 120 hr of heating at 110 °C. The improved capture capacity and kinetics, especially for desorption, as well as enhanced thermal stability of the non-aqueous system highlight its potential for industrial applications.